Molecular characterization and expression analysis of three subclasses of IgT in rainbow trout (Oncorhynchus mykiss) - Zhang, Nu (Dev Comp Immunol, 2017)
As the teleost specific immunoglobulin, IgT plays important roles in systemic and mucosal immunity. In the current study, in rainbow trout, we have cloned the heavy chain (Igτ) genes of a secretory form of IgT2 as well as the membrane and secretory forms of a third IgT subclass, termed IgT3. Conserved cysteine and tryptophan residues that are crucial for the folding of the immunoglobulin domain as well as hydrophobic and hydrophilic residues within CART motif were identified in all IgT subclasses. Through analysis of the rainbow trout genome assembly, Igτ3 gene was found localized upstream of Igτ1 gene, while Igτ2 gene situated on another scaffold. At the transcriptional level, Igτ1 was mainly expressed in both systemic and mucosal lymphoid tissues, while Igτ2 was largely expressed in systemic lymphoid organs. After LPS and poly (I:C) treatment, Igτ1 and Igτ2 genes exhibited different expression profiles. Interestingly the transcriptional level of Igτ3 was negligible, although its protein product could be identified in trout serum. Importantly, a previously reported monoclonal antibody directed against trout IgT1 was able to recognize IgT2 and IgT3. These data demonstrate that there exist three subclasses of IgT in rainbow trout, and that their heavy chain genes display different expression patterns during stimulation. Overall, our data reflect the diversity and complexity of immunoglobulin in trout, thus provide a better understanding of the IgT system in the immune response of teleost fish.